2019
DOI: 10.1021/acs.iecr.9b00712
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Water-Induced Mechanical Deterioration of Cardboard by a Sequential Polymer Treatment

Abstract: Paperboards and corrugated cardboard are some of the most used products in packaging today. Because of their geometry, i.e., undulations, they are mechanically robust and can sustain a significant amount of weight. However, exposure to water or humidity is highly destructive toward cardboard mechanical properties. Water-soaked corrugated cardboard can easily collapse with irreversible shape distortions. Various treatments have been developed to render cardboard hydrophobic including wax layers and nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Furthermore, previous works [7] reported how fluorine-containing coatings provide one of the lowest free-surface energies. Instead, regarding the T-POL and K-POL coatings, their contact angle ranged between 104-114 • , which is consistent with other polymeric coatings [16,18]. Although SG provides lower wettability, hence the water droplets easily slip off the substrate, the CA values generally did not show a correlation with Cobb test performance (excluding UC samples).…”
Section: Spectrophotometrysupporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, previous works [7] reported how fluorine-containing coatings provide one of the lowest free-surface energies. Instead, regarding the T-POL and K-POL coatings, their contact angle ranged between 104-114 • , which is consistent with other polymeric coatings [16,18]. Although SG provides lower wettability, hence the water droplets easily slip off the substrate, the CA values generally did not show a correlation with Cobb test performance (excluding UC samples).…”
Section: Spectrophotometrysupporting
confidence: 73%
“…Coatings can improve the corrugated cardboard water barrier and wet performance. Multiple works were done in the literature to improve corrugated cardboard water barrier properties [15][16][17][18][19][20]. The proposed solutions that were typically investigated used pigments and polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The tensile strength of paper-based materials generally decreases when they are exposed to high humidity [76,77]. Water also causes the elongation of paper to decrease [78]. Organic solvents tend to swell cellulose less than water: ethanol (83%) and toluene (2%) [79].…”
Section: Discussionmentioning
confidence: 99%
“…Corrugated cardboard can also be used as an interior building material and, when discarded, can be reused for pulp or paper [25]. Corrugated cardboard is known for its utility as a building material [25,26], and some studies have suggested the potential of hydrophobic treatment to avoid moisture absorption and further expand its versatility [27,28]. Moreover, it may act as a flame retardant, improving building safety [29].…”
Section: Introductionmentioning
confidence: 99%